MITYVAC DELIVERY SYSTEM VACUUM HANDLING OUR EXPERIENCE - Vidal Amat y León, Jorge (2015)
Our experience in managing Mityvac Vacuum Delivery System in 25 patients in the Peripheral Hospital SFP. "Augusto B. Legula" requiring assistance during the second stage, demonstrates the practical and simple handling and low cost, making it an essential tool in every delivery room to solve problems in the terminal stage of labor.